FLEXIBLE AND DISTRIBUTED SOFTWARE PROCESSES: OLD PETUNIAS IN NEW BOWLS? (Communications of the ACM, 2006)
The article discusses globally distributed software development, which allows computer software companies to develop high quality product for a cheaper price. While spreading software development across the globe makes economic sense for U.S. businesses, the practice brings with it many problems, including time differences, a lack of face-to-face time, and socio-cultural differences that can hamper projects. To mitigate the effects of these problems, managers adopt a flexible approach for software development.